Implementasi Storyytelling Dalam Karya Dibalik Dapur Kebab Factory.id Sebagai Sutradara - Fahrudin, Irfan Azis; Melano, Fiqie Lavani (eProceedings of Management, 2024)
Mass communication plays an important role in delivering information, entertainment, and education to the public.One of its derivative products is audiovisual content, such as company profile videos, which companies use tointroduce their products and enhance their image. Kebab Factory.ID, a kebab MSME in Bandung, has experienced adecline in sales since 2022 despite promoting through social media. This research aims to implement storytelling inthe company profile video